2010
DOI: 10.1371/journal.pone.0010600
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Promoters and Alternative Splicing: Hoxa5 Transcriptional Complexity in the Mouse Embryo

Abstract: BackgroundThe genomic organization of Hox clusters is fundamental for the precise spatio-temporal regulation and the function of each Hox gene, and hence for correct embryo patterning. Multiple overlapping transcriptional units exist at the Hoxa5 locus reflecting the complexity of Hox clustering: a major form of 1.8 kb corresponding to the two characterized exons of the gene and polyadenylated RNA species of 5.0, 9.5 and 11.0 kb. This transcriptional intricacy raises the question of the involvement of the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…1, F and H). In contrast, Hoxb5 expression remained unchanged in lungs from Even though mutant transcripts are produced from the Hoxa5 and Hoxb5 mutant alleles, both Hoxa5 and Hoxb5 mutations generate a null allele with no production of protein (11,43). We observed a loss of Hoxa5 expression in lungs from Hoxa5 Ϫ/Ϫ embryos and a reduced Hoxb5 expression in Hoxb5 Ϫ/Ϫ specimens that might reflect the interference of the neo selection cassette on Hox transcription as reported (Fig.…”
Section: Expression Of Hox5 Paralog Genes In the Developing Lungsupporting
confidence: 72%
“…1, F and H). In contrast, Hoxb5 expression remained unchanged in lungs from Even though mutant transcripts are produced from the Hoxa5 and Hoxb5 mutant alleles, both Hoxa5 and Hoxb5 mutations generate a null allele with no production of protein (11,43). We observed a loss of Hoxa5 expression in lungs from Hoxa5 Ϫ/Ϫ embryos and a reduced Hoxb5 expression in Hoxb5 Ϫ/Ϫ specimens that might reflect the interference of the neo selection cassette on Hox transcription as reported (Fig.…”
Section: Expression Of Hox5 Paralog Genes In the Developing Lungsupporting
confidence: 72%
“…Promoter competition and enhancer titration Hox clusters display very dense transcriptional activities, owing to the presence of numerous alternative transcription start sites and enhancers intermingled within the coding regions (Mainguy et al, 2007;Rinn et al, 2007;Coulombe et al, 2010). Accordingly, we find extensive transcription outside the annotated coding sequences of the HoxD complex, which contribute to delineate the two distinct transcription blocks.…”
Section: Research Article Development 139 (5)mentioning
confidence: 85%
“…The role of such a molecule is still unclear, as functional analysis in transgenic mice indicate that it is not able to activate the typical Hoxa10 patterning programme in the axial skeleton or interfere with it (Guerreiro et al, 2012). Hoxb3 and Hoxa5 also produce different mRNA isoforms through a combination of alternative splicing and alternative promoter usage; interestingly, the resulting isoforms are expressed in different domains during embryonic development (Chan et al, 2010;Coulombe et al, 2010;Sham et al, 1992), once again suggesting that the resulting isoforms might carry out specific functions. Finally, a recent bioinformatic study (P. Patraquim and C.R.A., unpublished) focused on mouse Hox genes revealed that approximately a third of them produce a spectrum of mRNA isoforms generated by different types of RNA processing, many of which are evolutionarily conserved between mouse and human.…”
Section: Review Development 140 (19) Review Development 140 (19)mentioning
confidence: 99%